2021
DOI: 10.1007/s00270-021-02926-x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Sclerotherapy of Venous Malformations of the Hand: A Multicenter Analysis

Abstract: Purpose To evaluate the safety and outcome of percutaneous sclerotherapy for treating venous malformations (VMs) of the hand. Materials and Methods A retrospective multicenter trial of 29 patients with VMs primarily affecting the hand, including wrist, carpus, and/or fingers, treated by 81 percutaneous image-guided sclerotherapies using ethanol gel and/or polidocanol was performed. Clinical and imaging findings were assessed to evaluate clinical response, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“… 18 A meta-analysis by Schmidt et al, however, concluded that sclerotherapy is both safe and effective in the treatment of these lesions, even when previous attempts have been made. 19 Guevara et al reported their overall complication rate following sclerotherapy of venous malformations of the hand and distal forearm in 17 patients who underwent a total of 40 procedures. They only noted two skin complications that had a complete resolution.…”
Section: Discussionmentioning
confidence: 99%
“… 18 A meta-analysis by Schmidt et al, however, concluded that sclerotherapy is both safe and effective in the treatment of these lesions, even when previous attempts have been made. 19 Guevara et al reported their overall complication rate following sclerotherapy of venous malformations of the hand and distal forearm in 17 patients who underwent a total of 40 procedures. They only noted two skin complications that had a complete resolution.…”
Section: Discussionmentioning
confidence: 99%
“…46 Thus, polidocanol is a mild sclerotherapy option, but may show similarly good treatment results after repeated sessions. 47,48 Bleomycin, a cytostatic agent belonging to the class of antibiotics, differs in its underlying sclerosing mechanism from the previously mentioned sclerosants. As dismantling the solid stroma of vascular structures, 49 it seems to be most efficient in comparatively spongiform VMs providing large stromal components.…”
Section: Venous Malformationsmentioning
confidence: 99%
“…46 Thus, polidocanol is a mild sclerotherapy option, but may show similarly good treatment results after repeated sessions. 47 48…”
Section: Interventional Treatment Optionsmentioning
confidence: 99%
“…Venous malformations (VM) are slow-flow vascular malformations according to the ISSVA (International Society for the Study of Vascular Anomalies) classification, with a prevalence of up to 1% in the overall population [ 1 , 2 , 3 ]. VM are congenital lesions consisting of dysplastic and dilated veins due to a disturbed vasculogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These agents harm dysplastic endothelial cells of VMs, causing intralesional thrombosis, inflammation, and scarring. Percutaneous sclerotherapy has proven to be effective even in challenging anatomic regions accompanied by a low risk profile [ 2 ]. However, many patients require several sessions of percutaneous sclerotherapy before improvement of clinical symptoms may be recognized.…”
Section: Introductionmentioning
confidence: 99%